Characterisation of Phytophthora capsici causing foot rot of black pepper (Piper nigrum L.) in Julau, Sarawak - Tu Anh, Vu Thanh; Jin Chi, Kong; Freddy Kuok San, Yeo; Kiong Hook, Kueh (Taylor & Francis group, 2022)
Phytophthora foot rot disease remains a deadly disease of black pepper in sarawak, a major pepper producing state in Malaysia. this study characterised three Phytophthora iso- lates, recovered from diseased plant tissues of foot rot infected pepper vines from two farms in Julau district, sarawak. the three isolates were confirmed to be Phytophthora capsici based on the distinct torulose hyphae characteristic and molecular analysis. the isolates exhibited various colony and sporangia morphologies and growth rates. two mating types were detected among the isolates based on the formation of oogonia in pairing tests between the isolates - one type associated with isolate i4 and i5 recovered from one farm and the second type with isolate e3 from the other farm. Virulence test indicated that i5 iso- late was relatively more virulent than e3 isolate. this study provides important information to assist in the development of effective management strategies for the disease.